2021
DOI: 10.3390/educsci11110657
|View full text |Cite
|
Sign up to set email alerts
|

The IARA Model Proved Effective in Emotional Literacy, Characters Strengths Awareness, and Cohesion among Italian Children

Abstract: Literature highlights how education in the twenty-first century begins to advocate multiple new concepts, such as new technology, new pedagogies, interdisciplinary curricula, open learning, etc. Among these concepts, the recognition and awareness about one’s character strengths are demonstrated to improve emotional management and individual/group’s quality of life. We studied three fifth-grade Italian classes using an emerging educational model called IARA to verify if it can truly improve emotional literacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…It is worth emphasize that AD is not a free drawing and it was used without any psychological or therapeutical purposes. According to the literature (De Giorgio et al, 2017b;Maulini et al, 2021;Padovan et al, 2018aPadovan et al, , 2018b, the AD has three precise phases so that the child can focus his responses only on illness, care pathway, and healing. Speech therapists do not intervene in the creative process, do not suggest anything, and do not explore areas of strictly psychological competence, leaving the PWS free to draw what he desires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth emphasize that AD is not a free drawing and it was used without any psychological or therapeutical purposes. According to the literature (De Giorgio et al, 2017b;Maulini et al, 2021;Padovan et al, 2018aPadovan et al, , 2018b, the AD has three precise phases so that the child can focus his responses only on illness, care pathway, and healing. Speech therapists do not intervene in the creative process, do not suggest anything, and do not explore areas of strictly psychological competence, leaving the PWS free to draw what he desires.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these used drawing in stuttering. In literature is emerging the IARA model (De Giorgio et al, 2017a;2017b;Barattucci et al, 2019;Padovan et al, 2018aPadovan et al, , 2018bMaulini et al, 2021), a person-focused care that -briefly, since widely demonstrated and described elsewhere -consists of a model that uses both some specific tools (i.e., awareness drawing, qualities, imagery, counseling, "3A rules") especially designed for the issue to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Education in the twenty-first century is beginning to advocate for new concepts, such as new technologies, new pedagogies, interdisciplinary curricula, and open learning. Among these concepts, recognition and awareness of the strength of one's character are shown to improve the emotions, management, and quality of life of individuals or groups (Maulini et al, 2021). Therefore, schools have an important task to prepare students, not only in terms of knowledge but also to strengthen character.…”
Section: The Influence Of the School Environment On Character Educationmentioning
confidence: 99%
“…Second meeting. During this one-hour meeting, one week after T0, the DNE aimed to raise awareness of the participants using some tools of transpersonal psychosynthesis theory [29] and the 3A rule (in Italian: Accoglienza, Ascolto, Accettazione incondizionata positiva; that is: hospitality, listening, positive unconditional acceptance [29]).…”
Section: Iara Interventionmentioning
confidence: 99%
“…The meeting took place 21 days after T0 and using the same reception principles already described, the DNE immediately gave the person the opportunity to narrate his experience of the disease and of any behavioral change regarding the injection Second meeting. During this one-hour meeting, one week after T0, the DNE aimed to raise awareness of the participants using some tools of transpersonal psychosynthesis theory [29] and the 3A rule (in Italian: Accoglienza, Ascolto, Accettazione incondizionata positiva; that is: hospitality, listening, positive unconditional acceptance [29]).…”
Section: Iara Interventionmentioning
confidence: 99%